2021
DOI: 10.1002/bmc.5294
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the main active components of Baoyuan decoction in plasma and urine of normal and heart failure rats

Abstract: The global morbidity and mortality of heart failure has been increasing in recent years. Traditional Chinese medicine (TCM) was increasingly used to treat cardiovascular diseases. Baoyuan decoction (BYD) was a famous classical prescription in China. Modern pharmacological studies showed that it had obvious therapeutic effects on cardiovascular diseases, but its pathological pharmacokinetic studies were unclear. In this research, the absorption of 16 bioactive components in plasma and the excretion of 9 represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, metabolism enzymes, transport proteins, cell membrane permeability, and gut microbiota are easily altered under pathological states, thereby affecting the absorption, distribution, metabolism, and excretion of the medical supplements and influencing their efficacy. 18–20 Interestingly, we found that the pharmacokinetic behaviors of the above compounds in the CUMS rats differed from those in normal rats after CDE and CTE administration. The relative bioavailability of the most absorbed compounds of CH under a depression-like state was generally higher, which are related with the pathological conditions in depressed rats, such as enhanced intestinal epithelial permeability, 21 gut microbiota dysfunction, 22 and CYP450 activity alternation, 23 but the specific mechanism remains to be further explored.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, metabolism enzymes, transport proteins, cell membrane permeability, and gut microbiota are easily altered under pathological states, thereby affecting the absorption, distribution, metabolism, and excretion of the medical supplements and influencing their efficacy. 18–20 Interestingly, we found that the pharmacokinetic behaviors of the above compounds in the CUMS rats differed from those in normal rats after CDE and CTE administration. The relative bioavailability of the most absorbed compounds of CH under a depression-like state was generally higher, which are related with the pathological conditions in depressed rats, such as enhanced intestinal epithelial permeability, 21 gut microbiota dysfunction, 22 and CYP450 activity alternation, 23 but the specific mechanism remains to be further explored.…”
Section: Discussionmentioning
confidence: 80%